Subcortical vascular dementia: Integrating neuropsychological and neuroradiologic data - Price, C.C. (2005)
BACKGROUND: Research criteria for subcortical vascular dementia are based on radiologic evidence of vascular pathology and greater impairment on tests of executive control than memory. The relationship(s) between neuroradiological evidence of subcortical vascular disease and neuropsychological impairments has not been specified. OBJECTIVE: To define these research criteria, the authors rated the severity of MRI white matter abnormalities (WMAs) and neuropsychological data from patients with dementia. METHODS: Sixty-nine outpatients who met the criteria for dementia were studied with neuropsychological tests that assessed executive (mental) control, declarative memory, visuoconstruction (clock drawing), and language (semantic category fluency). MRI-WMAs were rated using a leukoaraiosis (LA) scale (range 0 to 40). RESULTS: First, regression analyses demonstrated that neuropsychological measures accounted for 60.7% of the variance in WMA severity (47.3% of this variance attributable to executive/visuoconstructive test performance, 13.4% attributable to memory/language test performance). Second, patients were grouped according to the severity of WMAs (i.e., low, moderate, and severe white matter groups). Only patients with mild WMA (mean LA = 3.61 ± 2.63, approximately 2.4 to 15.6% of the subcortical white matter) presented with greater impairment on memory/language tests vs executive control/visuoconstructive tests, a neuropsychological profile typically associated with Alzheimer disease. Patients with moderate WMA (mean LA = 12.76 ± 2.49, approximately 25.6 to 38.1% of the subcortical white matter) presented with equal impairment on executive/visuoconstructional vs memory/language tests. Patients with severe WMA (mean LA = 21.76 ± 2.97, approximately 46.9 to 62.4% of the subcortical white matter) displayed a profile of greater executive/visuoconstructional impairment relative to memory/language disabilities. CONCLUSION: A profile of equal impairment on tests of executive control and memory along with radiologic evidence involving about one-fourth of the cerebral white matter as measured by the Leukoaraiosis Scale may be sufficient for a diagnosis of subcortical vascular dementia.